2023
DOI: 10.3399/bjgpo.2022.0186
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of clinical diagnosis of onychomycosis in Dutch general practice: a diagnostic accuracy study

Abstract: Background:Onychomycosis,the most common cause of nail dystrophy is generally diagnosed by clinical examination. Current guidelines for Dutch general practice advise confirmatory testing onlyin case of doubt or insufficient response to treatment. However, making a correct diagnosis can be challenging given the wide variety of clinical features and differential diagnosis.Aim:To establish accuracy of clinical diagnosis of onychomycosis by general practitioners (GPs).Design and Setting:A diagnostic accuracy study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In the current study, we observed a significant level of concordance Various studies, including those conducted by Watjer et al 4 Elewski et al 7 and Gupta et al 12 have conducted pre-and posttreatment assessments using the OSI scale. However, none of these studies specify the number of professionals who administered the OSI scale.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the current study, we observed a significant level of concordance Various studies, including those conducted by Watjer et al 4 Elewski et al 7 and Gupta et al 12 have conducted pre-and posttreatment assessments using the OSI scale. However, none of these studies specify the number of professionals who administered the OSI scale.…”
Section: Discussionsupporting
confidence: 78%
“…
The most characteristic clinical signs include nail thickening, subungual hyperkeratosis, nail plate discolouration and onycholysis. [1][2][3][4]6,7 Traditionally, ONM is typically classified based on these clinical signs through visual assessment. However, it is worth noting that there are numerical classifications available, though not all of them are validated.
…”
mentioning
confidence: 99%
“…By contrast, performing only a histopathologic examination is not able to provide genus-or species-level identification, and thus does not allow for more targeted treatment approaches. Amidst the current high risk of misdiagnosis and mistreatment of onychomycosis [13,15,16], a greater advocacy for laboratory testing is warranted to address these pressing challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Consequentially, more than half of onychomycosis patients reported to have self-diagnosed and self-treated their condition, which likely contributed to a high treatment failure rate of 24.0% [15]. The current healthcare burden is further compounded by a high rate of misdiagnosis (25.5%) among general practitioners [16] and a growing number of patients seeking care from specialists rather than primary care providers [17].…”
Section: Introductionmentioning
confidence: 99%